Knowledge and attitudes towards antiretroviral therapy among factory workers participating in a cohort on HIV and AIDS, Addis Ababa, Ethiopia. - Degefa, A; Sanders, E; Mekonnen, Y; Messele, T; Wolday, D; Dorigo-Zetsma, W; Mekonnen, W; Schaap, A; Dukers, N (2003)
This study investigates barriers that may pose a threat to a successful implementation of an antiretroviral treatment (ART) program in Ethiopia. As prelude to the provision of ART among factory workers participating in a cohort study on HIV and AIDS in Ethiopia, we measured knowledge and attitudes towards several aspects of ART and provided an educational intervention. The proportion of participants having good knowledge on issues concerning adherence was found reasonably good (67.7%), concerning the benefit of ART was intermediate (37.7%) and concerning eligibility was very low (16.8%). Knowledge concerning eligibility improved somewhat after the provision of the educational intervention. Only one third of HIV infected persons discloses their HIV status to their partner. Several aspects that could impact adherence to ART will be discussed, such as ART knowledge, social support, willingness to take ART, and disclosure of serostatus, taking the cohort study site into account. Results indicate a tremendous need to educate cohort participants before and during introduction of ART. Efforts to increase knowledge of ART, and especially knowledge of eligibility criteria to start ART, seem warranted, as well as encouragement to identify social support and disclose HIV serostatus, as these factors directly impact the success of an ART program.